KERAGAAN DAN BUDIDAYA KOMODITAS PANILI DI INDONESIA (Studi Kasus Kabupaten Minahasa) - ELIZABETH, ROOSGANDHA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005, 2012)
Indonesia might be considered estate crops country. Vanilla is one of estate crops commodity that has significant share of Indonesian foreign exchange revenue. This spicy commodity is one of Indonesian important traditional export commodities in international markets. As one of prospective export commodity Indonesia should give more attention to the development this commodity. The data shows recently, however, the trend of declining the export demand in the international market, both in volume and value. If it is compared to other Asian countries, moreover, the decline is shown very significant. In Minahasa district in particular, the decline is caused by, among others, traditional crop management system and technology, need high capital if it is cultivate intensively and integrated, and lack of labour knowledge on how to do the best practice in cultivating vanilla. More importantly, price uncertainty and market uncertainty, where up to present price is determined mostly by traders, give disincentive and discourage vanilla farmers to improve their cultivation practice.
Keywords: Pperforman, Cultivation, Vanilla Commodity, Mmarket and Price Uncertainty.